Karamojong Adolescents in Tororo, Uganda: Life Events, Adjustment Problems, and Protective Factors. Issue 4 (19th May 2017) - Eggum-Wilkens, Natalie D.; Zhang, Linlin; Farago, Flora
ABSTRACT: The Karamojong people of Uganda are marginalized and likely to have difficult lives. Research is needed to understand Karamojong children's challenges, adjustment, and resiliency to help guide interventions and policies to improve their lives. Thus, 18 Karamojong 10–16-year-olds (10 girls; M = 13.33 years; SD = 1.81) were recruited from a nongovernmental organization in Tororo District, Uganda, and interviewed about their life events, coping strategies, social support, and hope. Adolescents also were verbally administered questionnaires about their life events and adjustment problems. Participants reported many negative life events (M = 9.28 of 16). The number of negative life events was positively correlated with internalizing, but not with externalizing, problems. Participants described a variety of coping strategies. Most participants received emotional or instrumental social support, and were hopeful about their futures. Hardships were often alcohol- or poverty-related events, whereas hope was often centered on education.